EFSA's second Risk Assessment Research Assembly (RARA) delivered on its objectives. (April 2023) - Bronzwaer, Stef; Alves, Frederico; das Neves, Carlos G.; Byrne, Pamela; Url, Bernhard
Abstract: To stimulate alignment between European and national research strategies and funding efforts, EFSA brought together 250 food safety researchers, funders, policy/decision makers and risk assessors for a second Risk Assessment Research Assembly (RARA). With a panel of international experts RARA discussed: i) how food safety regulatory research can support the Sustainable Development Goals (SDGs) and relevant European policies; ii) how to foster alignment of research priorities and investments on food safety; and iii) how to reinforce and utilise the wider food safety risk assessment network. The RARA network plays a key role in facilitating the bilateral communication needed to develop research and policy agendas that feed into each other. Food safety actors support the necessary transition to sustainable food systems (i.e. SDGs & Green Deal). The global challenges threatening food systems call for more alignment between national and central efforts. RARA provided suggestions on how to overcome barriers in alignment and how to increase synergies amongst research programmes, in which the potential of European Partnerships were recognized and fully supported. The RARA network is a valuable asset for transdisciplinary cooperation across the science-policy-interface (scientists, risk assessors, policy makers), and across EU and national authorities. RARA 2022 demonstrated that its' research community is ready to support the transition to sustainable food systems and can be considered a valuable tool when programming future research agendas across Europe and member states. Highlights: Food safety actors support the necessary transition to sustainable food systems. EU Agencies with their national partners provide a sustainable network-of-networks. Risk assessors can facilitate communication between science and policy. Global challenges necessitate deeper alignment of EU and national research efforts. EFSA and its RARA community are an asset for identifying food research needs.